Review: Stress and Hypertension - Kamar, Haizul Haron; Wan Ahmad, Wan Azman; Tan, Kim Heung; Choy, Anna Maria; Chan, Chong Guan (Faculty of Medicine, University of Malaya, 2000)
Hypertension is a major cardiovascular risk factor that directly contributes to myocardial infarction, cerebrovascular accidents, congestive cardiac failure, peripheral vascular disease and premature mortality (I). In the great majority of cases, no cause can be found and this form of hypertension is termed 'primary' or 'essential' hypertension. Various theories have been put forward and the causes can be divided broadly into genetic and environmental factors. Based on twin studies, it was estimated that about 50 percent of blood pressure variance is genetic (2). The main environmental causes are dietary and psychosocial factors. In this review, we will concentrate on the latter while noting that there is still disagreement about the role of a dietary factor, sodium chloride, in causing hypertension. A metaM analysis of trials of sodium restriction concluded that sodium intake had no influence on blood pressure in normotensive subjects and in hypertensives below 45 years of age (3). We will also discuss an interesting phenomenon known as 'white coat hypertension'.